PRINSIP PENGELOLAAN KEUANGAN SEKOLAH DALAM PERSPEKTIF ISLAM - Rahmawati, Alfera; Azril, Iman; Agustiana, Afifah Yoga; Andriesgo, Johan; Gustia, Aini; Mukhlisin, Mukhlisin; Wahyuni, Suri Eka (STKIP Pesisir Selatan, 2025)
To realize quality education, one way is to optimize the school budget as a form of effective and efficient use of resources to support all aspects of school learning and development activities. The principle of school financial management is an important foundation in managing the flow of school finances to maintain the optimization of the use of funds so that they are right on target and achieve educational goals. The purpose of this study is to find out what are the principles of school financial management in the Islamic perspective. The research method used is a qualitative descriptive approach through library research, the results of the study show that there are several principles of financial management in the general view and in the Islamic perspective. In the general view there are six principles of financial management; 1. Justice, 2. Efficiency, 3. Effectiveness, 4. Transparency, 5. Accountability, and 6. Participation While in the Islamic view there are six 1. The principle of belief in the rules of Allah SWT, 2. The principle of Adl, 3. Amanah, 4. Sidiq, 5. Fatonah, and 6. Tabliq. These two Padangans have differences and similarities whose only difference lies in the Islamic orientation which is not only worldly, but also ukhrawi, thus making financial management a form of worship and trust in Allah SWT.